2015
DOI: 10.1117/1.nph.2.1.015007
|View full text |Cite
|
Sign up to set email alerts
|

Infrared neural stimulation of human spinal nerve rootsin vivo

Abstract: Abstract. Infrared neural stimulation (INS) is a neurostimulation modality that uses pulsed infrared light to evoke artifact-free, spatially precise neural activity with a noncontact interface; however, the technique has not been demonstrated in humans. The objective of this study is to demonstrate the safety and efficacy of INS in humans in vivo. The feasibility of INS in humans was assessed in patients (n ¼ 7) undergoing selective dorsal root rhizotomy, where hyperactive dorsal roots, identified for transect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 48 publications
2
61
0
Order By: Relevance
“…Infrared neural modulation (INM) in particular offers both neural stimulation and inhibition without introducing exogenous agents. Infrared neural stimulation (INS) has shown to be an effective method for stimulating action potentials in many animal models [23][24][25][26][27][28][29], and has been applied in human dorsal rootlets [30], but its complementary technique, infrared neural inhibition (INI), has yet to be translated for human use due to the temperature rise required for therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Infrared neural modulation (INM) in particular offers both neural stimulation and inhibition without introducing exogenous agents. Infrared neural stimulation (INS) has shown to be an effective method for stimulating action potentials in many animal models [23][24][25][26][27][28][29], and has been applied in human dorsal rootlets [30], but its complementary technique, infrared neural inhibition (INI), has yet to be translated for human use due to the temperature rise required for therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It seems likely that differences in the biological preparation used, the method used to assay neuronal activation, and the parameters used for laser stimulation have contributed to this debate. Nonetheless, interest remains, as indicated by recent studies examining the applicability of INS for human neuroprostheses [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…293 Finally, early trials in humans have shown that INS can be used to stimulate human dorsal root ganglia. 294 Although the research surrounding INS is promising, clinical applications of INS would require constant stimulation at 12–15 Hz, placing it above the upper threshold for injury. 295 An alternative to bypass these limitations has been proposed that combines INS with extraneural stimulation via nerve cuff.…”
Section: Future Interfaces: Novel Paradigmsmentioning
confidence: 99%